A complex variable boundary element method (CVBEM) for solving seepage problems - Lee, Lin Jye (Universiti Malaysia Sarawak (UNIMAS), 1998)
In the present project, the complex variable boundary element method (CVBEM) is applied to solve some seepage problems involving earth dams. The method is based on the Cauchy integral formulae. It reduces the seepage problems to the task of solving a system of linear algebraic equations. The coefficients of the linear algebraic equations can be easily computed. Hence the CVBEM for the seepage problems can be easily implemented on the computer.